From an Antimicrobial Agent to a constituent of 3D Printed Heterogenous Scaffolds Stimulating Bone Characteristics: An In-vitro and Animal model evaluation - Shahad Ahmed Daood; Martha Then Xin Yi; Nicole Wen Ce Mun; Sharjeel Ilyas; Lee Yin Shien; Oh Jia En; Syed Saad Bin Qasim; Yichen Dai; Galvinderjeet Kaur Grewal; Ng Mei Liit; Gopu Sriram; Malikarjuna Rao Pichika; et al. (Regenerative Therapy)
This paper describes a promising candidate molecule, investigates the pattern of scaffold composition which arises and assesses the effect of the agent on its mechanical properties. Methods: Scaffold samples were fabricated using a commercial extrusion bioprinter equipped with a pneumatic printhead fitted with a 21G conical nozzle. The Pore Printability Index, and the area and perimeter of the pore within the grid patterns were quantified using ImageJ software (NIH, USA). Mechanical properties of scaffolds were assessed using atomic force microscopy. The phase composition and crystal structures were analyzed using X-ray diffraction and Raman mapping. Morphologies of human gingival fibroblastic cells were examined using scanning electron microscopy. Lactobacillus biofilms were generated for cytolysin peptide cleavage. A rabbit bone defect model with scaffold implantations was used to provide histologic specimens for measuring percentages of bone trabeculae, collagen fibers and inflammatory cells along with granulation tissue. The Primeway Total RNA Extraction Kit was used for RNA extraction. Results: All bioink formulations demonstrated successful printing of 3D grid and solid square patterned scaffolds achieving Pr values exceeding 0.9. 0.1 %K21 group showed the highest elastic modulus. XRD revealed a pattern producing around 90 % β-tricalcium phosphate displaying two peaks at 2θ angles. 0.1 % K21 and 0.1 %CHX did not alter scaffold's pore size and porosity. 0.1 %K21 group exhibited highest ratio (62.5 ± 6.1 θ), significantly surpassing control. Surface morphologies of cells were also well retained. TEM image shows a sequence of structural changes in fibroblastic cell structure when exposed to K21. 0.1 % K21 proved to be critical in completely eradicating the biofilm. 0.K21 group closed the openings of wound areas completely. Correlation coefficient of gene expression levels demonstrates sample variations and recurring instances among groupings. Conclusion: 3D-printing technologies with 0.1 %K21 represent a significant advancement over conventional regenerative medicine techniques for bone-related treatments.